Effects of Alcoholic Extracts of Cinnamomum zeylanicum and Origanum Majorana on Expression of Hly Gene in Escherichia coli - Luma Saeed Mohammed1 , Enass Ghassan Sweedan1, May Talib Flayyih2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Escherichia coli isolates isolated from urinary tract infection identified by biochemical test and confirmed by vitek 2 compact system. Minimum inhibitory concentrations of Cinnamomum zeylanicum and Origanum majorana alcoholic extracts determined by broth macrodilutionassay ,it range (12.5-25)mg/ml for C. zeylanicum and 100mg/ml for O.majorana leaves. The expression of hly gene studied in presence of 16srRNA as reference gene, four isolates of E.coli (A1 ,A2,A5 and A6)used to detect the expression of hly gene by using Quantitative reverse transcription-PCR(1-StepqRT-PCR) before and after tereatment with plants extracts calibrated with 16srRNA. There was inhibition in hly gene expression with O.majorana,the fold changes were 1.23 and 2 in isolates A5 and A6respectively while there were induction in hly gene expression with C. zeylanicum,the fold changes were 137 and 73.5 for isolates A1 and A2 respectively.